2019
DOI: 10.1017/brimp.2019.18
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sex-Based Differences in Concussion Knowledge, Attitudes and Resources in Young First Nations Hockey Players: A Cross-Sectional Survey from Ontario, Canada

Abstract: Objective:Indigenous youth are vulnerable to concussion when playing hockey. A clear characterisation of sex differences among Indigenous youth could assist in tailoring future education programmes for prevention and management of concussion. The purpose of this study was to compare and contrast concussion knowledge, attitudes and resources in First Nations girls and boys playing recreational hockey.Method:The cross-sectional survey was conducted in partnership with a First Nations’ chief, other Indigenous com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…Whilst this research aligns with studies which have shown no, or only slight, differences in the overall attitudes towards concussion expressed by males and females, 9,15,33 it also supports previous research identifying gender differences in attitudes to specific issues. For example, Hunt et al found that females are more likely than males to report concussions, 15 and Sanderson et al 14 and Jorgensen et al 12 concluded that females are more likely than males to continue playing sport when concussed. Similarly, Hunt et al 15 found that boys expressed a greater concern over the seriousness of concussions, and O’Connor and Molloy 33 noted that females reported worrying more about the potential long-term effects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Whilst this research aligns with studies which have shown no, or only slight, differences in the overall attitudes towards concussion expressed by males and females, 9,15,33 it also supports previous research identifying gender differences in attitudes to specific issues. For example, Hunt et al found that females are more likely than males to report concussions, 15 and Sanderson et al 14 and Jorgensen et al 12 concluded that females are more likely than males to continue playing sport when concussed. Similarly, Hunt et al 15 found that boys expressed a greater concern over the seriousness of concussions, and O’Connor and Molloy 33 noted that females reported worrying more about the potential long-term effects.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Hunt et al found that females are more likely than males to report concussions, 15 and Sanderson et al 14 and Jorgensen et al 12 concluded that females are more likely than males to continue playing sport when concussed. Similarly, Hunt et al 15 found that boys expressed a greater concern over the seriousness of concussions, and O'Connor and Molloy 33 noted that females reported worrying more about the potential long-term effects. Whilst others have questioned the reliability of the RoCKAS-ST attitudes measure, 6 the complexity of this relationship revealed across studies suggests that it is an oversimplification to consider attitudes as a binary choice between safety and risk.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation